Cyclic redox scheme towards shale gas reforming: a review and perspectives. Issue 12 (30th October 2020) - Qin, Lang; Cheng, Zhuo; Baser, Deven; Goldenbaum, Tyler; Fan, Jonathan A.; Fan, Liang-Shih
Abstract : Alkanes are potential precursors to many value-added chemicals such as olefins and other petrochemicals. Abstract : Alkanes are potential precursors to many value-added chemicals such as olefins and other petrochemicals. However, the conversion of light alkanes can be challenging due to their strong C–H bonds. Chemical looping technology based on cyclic redox schemes is an attractive platform that utilizes metal oxides as oxygen carriers for clean and effective fuel processing. Chemical looping systems can potentially be operated over a wide range of reaction conditions with a lower capital and operating cost under a reduced energy and environmental penalty. The reactivity and long-term performance of the oxygen carriers are key for the successful deployment of the chemical looping technology. This work reviews the recent advances in chemical looping alkane utilization including chemical looping partial oxidation (CLPO) of methane, chemical looping oxidative coupling of methane (CLOCM) and oxidative dehydrogenation (CLODH) of ethane, propane and butane. In particular, material design, mechanistic insights of the reactions, and associated reactor configurations for the reactions are discussed. The perspective viewpoints are also given on the viability of the cyclic redox schemes for shale gas dehydrogenation/reforming applications.